STRATEGI GURU FIKIH MENGGUNAKAN CANVA SEBAGAI MEDIA PEMBELAJARAN KREATIF - Lonie Anggita; Ediansyah; Moch Iqbal (Program Studi Manajemen Pendidikan Islam, 2025)
This research aims to understand how Fiqh teachers use Canva as a creative learning medium with a qualitative approach. Canva is a web-based graphic design platform and mobile app that makes it easy for users, including teachers and students, to create different types of visual content such as posters, presentations, infographics, videos, and other learning materials in a very easy and fast way. Through Canva, students become more interested and easy to understand Fiqh material which was previously often considered complicated and boring, The method used is a case study with data collection techniques in the form of interviews, observations, and documentation of teachers and students in madrasas. Research found that teachers use various Canva features, such as video creation, and interactive slides, to deliver Fiqh material in a more engaging and enjoyable way. This strategy has a positive impact on a more lively learning atmosphere and increases student active engagement. However, teachers face several obstacles, such as limited technological capabilities and the time required to prepare materials, which can be overcome through training and cooperation with peers. Through this media, students are more involved in learning activities, dare to express opinions, and are able to understand Fiqh concepts in a more contextual and fun way. These findings affirm the importance of using technology in religious education to support the needs of 21st-century learning that prioritizes creativity, communication, and collaboration. The implications of the study show the need for teacher capacity building and the provision of ongoing technical support to ensure that the implementation of Canva-based learning media can be effective and consistent. In conclusion, Canva is an effective tool to help Fiqh teachers create innovative and engaging learning with an in-depth qualitative approach.